2011
DOI: 10.1111/j.1537-2995.2011.03355.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus transmission by blood transfusion during 4 years of individual‐donation nucleic acid testing in South Africa: estimated and observed window period risk

Abstract: We report the first known case of transfusion-transmitted HBV infection by blood screened using ID-NAT giving an observed HBV transmission rate of 0.34 per million. The estimated pre-acute-phase transmission risk in the ID-NAT screened donor population was 73-fold higher than the observed WP transmission rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
111
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(116 citation statements)
references
References 39 publications
(104 reference statements)
4
111
1
Order By: Relevance
“…A much higher HBsAg prevalence (8.1%) was detected in 480 healthcare workers investigated by Kondili et al [62] in 2004 in Albania, in accordance with the widespread of HBV infection in this country. In this study, the highest rates of HBsAg positivity were found in the youngest age group (11.4% in the aged [20][21][22][23][24][25][26][27][28][29][30] and in the auxiliaries (12.6%), but a high HBsAg prevalence (7.2%-7.5%) was also found in the healthcare workers aged over 30. The anti-HBc seroprevalence was also extremely high (70%) in this study and was associated with an age over 40 (OR = 2.9; 95%CI: 1.9-4.6).…”
Section: Studies On Hbv Infection In Healthcare Workersmentioning
confidence: 96%
See 1 more Smart Citation
“…A much higher HBsAg prevalence (8.1%) was detected in 480 healthcare workers investigated by Kondili et al [62] in 2004 in Albania, in accordance with the widespread of HBV infection in this country. In this study, the highest rates of HBsAg positivity were found in the youngest age group (11.4% in the aged [20][21][22][23][24][25][26][27][28][29][30] and in the auxiliaries (12.6%), but a high HBsAg prevalence (7.2%-7.5%) was also found in the healthcare workers aged over 30. The anti-HBc seroprevalence was also extremely high (70%) in this study and was associated with an age over 40 (OR = 2.9; 95%CI: 1.9-4.6).…”
Section: Studies On Hbv Infection In Healthcare Workersmentioning
confidence: 96%
“…Worthy of note, the screening of blood donors for markers of HBV infection has dramatically reduced the risk of HBV transmission through the transfusions of blood and blood products. At present, this risk is estimated as 1-4 cases per million blood components transfused in low-prevalence areas [29] and around 1 case per 20000 blood transfusions in high-prevalence regions [30] . The transfusion of infected blood and blood products was the most prominent route of transmission of HCV infection until 1989 [1,31] .…”
Section: Risk Factors For the Acquisition Of Hbv And Hcv Infectionmentioning
confidence: 99%
“…More recently, the HBV ID NAT yield was estimated more precisely at 1 : 19.608, of which 1 : 25.627 in pre-anti-HBc and 1 : 83.473 in post-anti-HBc window period [7].…”
Section: Developing Countries Among Developing Countries Thementioning
confidence: 99%
“…During the decade of 1990, all developed and the majority of the developing countries have improved HIV screening with p24 component added to the enzyme immunoassays. The second half of the decade was marked by the development of nucleic acid testing (NAT) technology in blood bank setting, mainly for HIV and hepatitis C virus (HCV), but also for HBV in the developed countries [6,7]. As public risk perception of transfusional risk sets high standards for the HIV, it eventually elevated blood safety standards for other diseases transmissible by blood transfusion, including HBV.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation